(untitled) (Journal of Contemporary Philology, 2021)
This paper provides a comparative analysis of the discourse markers you know in English and e di in Albanian. Although it belongs to the inventory of discourse markers that have received due attention in English scholarship and thus represents one of the most analyzed discourse markers, its Albanian equivalent has remained largely understudied in the context of spoken interaction. Therefore, the existing research on you know may serve as a basic framework for contrastive analyses of interpersonal functions of its functional counterparts in other languages. The main hypothesis underlying our investigation is that in both languages the markers have a common basic function: appealing to common knowledge and thus marking interpersonal relationships. To prove the hypothesis we conduct an analysis using data collected from authentic telephone conversations in Albanian whereby determining the interpersonal functions of e di and comparing them to the functions of you know. The results confirm the main hypothesis and support the distinction of several functions of e di in everyday conversation.